Microleakage at the etched enamel-resin interface with bonded orthodontic brackets - Lee Steven M.H; Freer Terence J.; Basford Kay E. (Sciendo, 1986)
This study was undertaken to investigate microleakage at the etched enamel-resin interface of directly bonded orthodontic brackets using a 2% aqueous fluorescein solution as a tracer. The buccal surfaces of 3 groups of30 extracted premolar teeth were etched and Begg plastic brackets were directly bonded. One group was kept in Hanks' Balanced Salt solution for 24 hours at 37 degrees C (24 hour control group). Another group was thermally cycled between 4 degrees C and 60 degrees C for 200 minutes (thermal cycling group). The last group was aged in Hank's Balanced Salt solution for 3 months at 37 degrees C (3 months aging group). Each tooth was then sectioned bucco-lingually through the centre of the bracket and the section was examined with an ultraviolet light microscope. The depth of fluorescein penetration along the enamel- resin interface was measured using a calibrated eyepiece graticule.